COMPARATIVE ANALYSIS OF STEVENS-JOHNSON SYNDROME INCIDENCE AMONG SEIZURE PATIENTS ON DIFFERENT ANTIEPILEPTIC DRUGS - JITENDER SHARMA; ANMOL SHARMA; SINDHU SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Steven-Johnson syndrome (SJS) is a severe, immune-mediated hypersensitivity reaction which is often triggered by medications, notably antiepileptic drugs (AEDs). AEDs such as phenytoin, carbamazepine, and sodium valproate are reported to be commonly offending drugs, particularly in individuals with genetic factors such as HLA-B*1502. A retrospective analysis of 1000 seizure patients revealed variability in SJS incidence among AEDs, highlighting levetiracetam as relatively safer but not risk-free. Early detection and tailored treatment can improve outcomes and mitigate risks. Methods: This retrospective study (2019–2024) at a tertiary care center examined the incidence of SJS in epilepsy patients aged ≥18 years treated with phenytoin, carbamazepine, sodium valproate, or levetiracetam for ≥6 months. Using electronic health records, patient demographics, AED patterns, and genetic predispositions (HLA-B*1502 allele) were analyzed. The study identified SJS rates and potential risk factors. For statistical analysis, p<0.05 was taken as significant. Results: An overall SJS incidence of 3.0%. Phenytoin (4.8%) and carbamazepine (3.6%) had significantly higher SJS rates than sodium valproate (2.4%) and levetiracetam (1.2%) (p<0.01). HLA-B*1502 allele strongly correlated with SJS, especially for phenytoin and carbamazepine. Age and comorbidities were not statistically significant risk factors. Genetic predisposition was the primary determinant of SJS risk, emphasizing personalized treatment strategies. Conclusion: There was a higher risk of SJS with phenytoin and carbamazepine compared to sodium valproate and levetiracetam, with levetiracetam being the safest option. Genetic screening for HLA-B*1502 in at-risk populations is essential to prevent SJS.